Zuogui Jiangtang Shuxin formula Ameliorates diabetic cardiomyopathy mice via modulating gut-heart axis - Huang, Ya-lan; Xiang, Qin; Zou, Jun-ju; Wu, Yongjun; Yu, Rong (Frontiers in Endocrinology, 2023)
Background: There is growing evidence demonstrating that the gut microbiota plays a crucial role in multiple endocrine disorders, including diabetic cardiomyopathy (DCM). Research shows that the Chinese herb reduces disease occurrence by regulating intestinal flora. Zuogui Jiangtang Shuxin formula (ZGJTSXF), a Chinese medicinal formula, has been clinically used for treatment of DCM for many years. However, there is still no clear understanding of how ZGJTSXF treatment contributes to the prevention and treatment of DCM through its interaction with gut microbiota and metabolism. Methods: In this study, mice models of DCM were established, and ZGJTSXF's therapeutic effects were assessed. Specifically, serum glycolipid, echocardiography, histological staining, myocardial apoptosis rate were assessed. Using 16s rRNA sequencing and high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS), we determined the impact of ZGJTSXF on the structure of gut microbiota and metabolites. The mechanism of ZGJTSXF action on DCM was analyzed using quantitative real-time PCR and western blots. Results: We found that ZGJTSXF significantly ameliorated DCM mice by modulating gut-heart axis: ZGJTSXF administration improved glycolipid levels, heart function, cardiac morphological changes, inhibited cardiomyocytes apoptosis，and regulate the intestinal microbiome in DCM mice. Specifically, ZGJTSXF significantly reduced the abundance of Alistipes closely related to TMAO production. Furthermore, ZGJTSXF alleviated DCM in mice by blunting TMAO / PERK / FOXO1 signaling pathway genes and proteins. Conclusion: ZGJTSXF administration could ameliorate DCM mice by remodeling gut microbiome structure, reducing plasma TMAO generation and suppressing TMAO/PERK/FOXO1 signaling pathway.